The level of administrative creativity of secondary school principals in Sabya governorate - Ghalti, Hussein Mohamed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to know the level of availability of the ingredients (elements) of creativity among managers, the level of their practice of the administrative creativity process, and the obstacles that limit their practice of the administrative creativity process. The researcher used the descriptive method, and the study sample consisted of (44) principals from the original community of principals in Sabya governorate, and a sample of teachers (285) from the original community of teachers, and the selection of all school administration supervisors and their number (9) educational supervisors, so a total sample Study (338). The study relied on two tools the questionnaire applied to teachers and managers, and the interview with the administrators of school management, and the study found a range of results: the level of elements of management innovation, the managers came to a fair degree, managers exercised the administrative process of innovation medium degree, and facing the practice of managers of administrative obstacles to creativity With a moderate degree, and that most of the obstacles hindering the practice of managerial creativity, organizational obstacles, and recommendations: The Education Department should choose secondary school principals from conscious educational leaders, who believe in the importance of administrative creativity in schools, and the researcher recommends the Ministry of Education and Education Departments to give school principals powers Commensurate with their responsibilities, allowing them the opportunity to show their creativity.
Keywords: creativity; administrative creativity; school principals; secondary stage